1989
DOI: 10.1007/bf02309918
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic threshold and the determination of training target heart rates in premenarchal girls

Abstract: The capability of children to respond to endurance training with increased aerobic capacity is unclear. Prepubertal subjects may require higher target heart rates than adults to increase VO2 max, and previous studies failing to demonstrate aerobic trainability in children may have involved inadequate exercise intensity. In this study, heart rates at the anaerobic threshold, measured noninvasively as the ventilatory breakpoint (VBP), were determined during treadmill testing of 12 premenarchal girls to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Among all included trials, 12 studies (60%) used the Tanner-Whitehouse evaluation scale to analyze children's maturation. 20 One study chose the Weber method, 21 whereas one identified the sample as pre-menarchal and therefore this analysis considered the population as prepubertal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Among all included trials, 12 studies (60%) used the Tanner-Whitehouse evaluation scale to analyze children's maturation. 20 One study chose the Weber method, 21 whereas one identified the sample as pre-menarchal and therefore this analysis considered the population as prepubertal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…20 One study chose the Weber method, 21 whereas one identified the sample as pre-menarchal and therefore this analysis considered the population as prepubertal. 23 The remaining 7 trials provided no evaluation of maturation, as shown in 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VAT may be used to establish a target heart rate for aerobic training and rehabilitation programs [5,17]. It also has been used to estimate aerobic fitness in subjects who otherwise would not tolerate maximal exercise testing [14], and it has been used to provide training guidelines for athletes [9,18].…”
Section: Ventilatory Anaerobic Thresholdmentioning
confidence: 99%
“…The percentage of "QO2m~ corresponding to the anaerobic threshold differs in children depending on whether ventilatory criteria [2,3,24,27,29] or lactate criteria [8,19,28] are employed, the latter resulting in distinctly higher percentages than ventilatory criteria. Whether or not anaerobic threshold can be substituted by ventilatory anaerobic threshold or whether agreement between the two is purely coincidental is still controversial [22].…”
Section: Discussionmentioning
confidence: 99%